Misplaced IUCD incidence, presentation and complications - Gupta, N; Gupta, T; Gupta, S; Jain, J; Wahi, S (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Intra uterine contraceptive device is important part of family planning services in India. They can be inserted post menstrually, post abortal, post-delivery or in post puerperal period. Despite of numerous advantages, IUCD is still not easily accepted because of associated complications, like increased bleeding, pain, infection, expulsion, perforation of uterine wall and migration to adjacent organs. MATERIAL AND METHODS: It was a prospective observational cross sectional study carried out in the department of Obstetrics & Gynecology at ESIPGIMSR, Basaidarapur, New Delhi for period of 3 years. All patients referred or presented with lost string or misplaced IUCD were enrolled. RESULTS: In our series, device was found in cervical canal in seven (9.45%) patients while 66 patients had IUCD in uterine cavity. It was removed by curettage or retrieval hook in 54 (72.97%) patients while in 12 (16.21 % ) patients, it was removed by hysteroscope. In one (1.35%) patient, IUCD had migrated to abdominal cavity and required laparoscopy followed by laparotomy, as it was stuck to omentum. CONCLUSIONS: Misplaced IUCDs are a common problem. A regular follow up of IUCDs for visible threads would help in earlier detection of misplaced IUCD and prevent long term consequences. Hysteroscopy will aid both in diagnosing and removal of misplaced IUCD. DOI: http://dx.doi.org/10.3126/jucms.v2i1.10486 Journal of Universal College of Medical Sciences (2014) Vol.2(1): 20-23